NUMERICAL SOLUTION OF SERIES L−C−R EQUATION BASED ON HAAR WAVELET - Berwal, Naresh; Panchal, Dinesh; Parihar, C.L. (Italian Journal of Pure and Applied Mathematics, 2013)
Haar wavelet is the simplest and computer oriented tool for solving ordinary diﬀerential equations and partial diﬀerential equations. Numerical solution of Series L−C−R is very useful in many engineering branches. In this paper we shall discuss the numerical solution of series L−C−R circuit with Haar wavelet method. We shall find charge in series L−C−R circuit at diﬀerent times. Two diﬀerent cases show the accuracy of Haar method.